2008
DOI: 10.1096/fasebj.22.1_supplement.1136.4
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of a tepary bean (Phaseolus acutifolius) lectin on human cancer cell lines

Abstract: Lectins can specifically recognize carbohydrates of cell membranes and some of them exhibit anticancer properties. In a previous work, we identified a cytotoxic lectin from tepary bean with differential antiproliferative effect on normal and transformed fibroblasts. The goal of the present work was to evaluate the effect of a concentrated tepary bean lectin fraction (TBLF) on human cancer cell lines growth. TBLF was obtained by molecular weight exclusion and ion exchange chromatography and it was tested on bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Specifically, the findings show that the colon cancer cell lines (CaCo 2 ) were the most sensitive, requiring less quantity to reach lethal concentration 50 (LC 50 ) and inhibitory concentration 50 (IC 50 ), followed by breast cancer cell lines (ZR-75 and MCF-7) [4,9]. In another study, a differential effect was observed between CaCo-2 cells and nontransformed ileum cells (IEC-18) [10]. An inhibitory effect on the proliferation of colon cancer cells (SW-480) has also been reported after 48 h of exposure to Tepary bean lectins [11].…”
Section: Introductionmentioning
confidence: 94%
“…Specifically, the findings show that the colon cancer cell lines (CaCo 2 ) were the most sensitive, requiring less quantity to reach lethal concentration 50 (LC 50 ) and inhibitory concentration 50 (IC 50 ), followed by breast cancer cell lines (ZR-75 and MCF-7) [4,9]. In another study, a differential effect was observed between CaCo-2 cells and nontransformed ileum cells (IEC-18) [10]. An inhibitory effect on the proliferation of colon cancer cells (SW-480) has also been reported after 48 h of exposure to Tepary bean lectins [11].…”
Section: Introductionmentioning
confidence: 94%